TINJAUAN HUKUM EKONOMI ISLAM PADA POLA JUAL BELI JAGUNG KUNING (STUDI KASUS DESA MALALA KABUPATEN TOLI-TOLI) - Nasrul; Sapruddin; Fadliah Mubakkirah (Tadayun: Jurnal Hukum Ekonomi Syariah, 2020)
Malala Village is an area in Dondo sub-district, Tolitoli district, where some of the people earn income from farming. One of them is Corn. The results of the corn farming activity are then traded through collectors. In this corn trading system there is a difference in the bargaining position of each farmer, namely farmers who receive seed capital assistance from collectors get a lower bargaining position, in exchange they get groceries from collectors according to the agreement at the beginning of the agreement, while farmers without seed assistance from collectors get a normal bargaining position. Farmers who get a low bargaining position feel disadvantaged, but they continue to do so because they do not have seed capital. This buying and selling system has become a habit of the local community. According to researchers, the pattern of buying and selling corn in Malala Village is not in accordance with the true teachings of Islam. Even though there is a mutualism symbiosis here, there are still parties who feel disadvantaged. The pattern of buying and selling yellow maize in Malala Village is not in accordance with several principles of sharia economic law. Because the conditions in the cooperation agreement contract are not fulfilled and have the principle of honesty and state their claim to the principles of a taradin minkum and la tazhlimuna wa la tuzhlamun on the aspects of buying and selling patterns between farmers and collectors.